COVID‐19 lockdown consequences on body mass index and perceived fragility related to physical activity: A worldwide cohort study - Constanta Urzeala; Martine Duclos; Ukadike Chris Ugbolue; Aura Bota; Mickael Berthon; Keri Kulik; David Thivel; Reza Bagheri; Yaodong Gu; Julien S. Baker; Nicolas Andant; Bruno Pereira; et al. (Wiley, 2022)
Abstract Background This paper is a follow‐up study continuing the COVISTRESS network previous research regarding health‐related determinants. Objective The aim was to identify the main consequences of COVID‐19 lockdown on Body Mass Index and Perceived Fragility, related to Physical Activity (PA), for different categories of populations, worldwide. Design The study design included an online survey, during the first wave of COVID‐19 lockdown, across different world regions. Setting and participants The research was carried out on 10 121 participants from 67 countries. The recruitment of participants was achieved using snowball sampling techniques via social networks, with no exclusion criteria other than social media access. Main outcome measures Body Mass Index, Physical Activity, Perceived Fragility and risk of getting infected items were analysed. SPSS software, v20, was used. Significance was set at P < .05. Results Body Mass Index significantly increased during lockdown. For youth and young adults (18‐35 years), PA decreased by 31.25%, for adults (36‐65 years) by 26.05% and for the elderly (over 65 years) by 30.27%. There was a high level of Perceived Fragility and risk of getting infected for female participants and the elderly. Correlations between BMI, Perceived Fragility and PA were identified. Discussion and Conclusions The research results extend and confirm evidence that the elderly are more likely to be at risk, by experiencing weight gain, physical inactivity and enhanced Perceived Fragility. As a consequence, populations need to counteract the constraints imposed by the lockdown by being physically active.